Statin use is associated with less postoperative cardiac arrhythmia after total hip arthroplasty. Issue 6 (November 2019) - Chen, Michael J; Bala, Abiram; Huddleston, James I; Goodman, Stuart B; Maloney, William J; Aaronson, Alistair J; Amanatullah, Derek F
Introduction: While statins have been found to reduce postoperative atrial fibrillation after cardiac surgery, little is known about their use in total hip arthroplasty (THA). This study investigated if statins would similarly reduce postoperative arrhythmias in patients undergoing THA. Methods: We queried a large Medicare and private-payer database from 2005 to 2012 and identified 12, 075 patients who were on a statin prior to THA. We then age and sex matched 34, 446 non-statin users who underwent THA. Baseline comorbidities and postoperative complications were obtained and assessed via standard descriptive statistics. Results: The statin users had more preoperative comorbidities including congestive heart failure, valvular heart disease, pulmonary and renal disease, diabetes, hypertension, obesity, and anaemia (all p values < 0.001). Postoperatively, the statin users had a statistically higher 90-day incidence of transfusion, acute renal failure, heart failure, pneumonia, and sepsis/shock. All new-onset cardiac arrhythmia was significantly less frequent in the statin group at 2 weeks (3.88% vs. 4.72%, p < 0.001), 30 days (4.47% vs. 5.29%, p < 0.001), and 90 days (5.44% vs. 6.31%, p = 0.001) postoperative. There was no difference in the frequency of venous thromboembolism, myocardial infarction, postoperative anaemia, or bleeding at 90 days postoperative. Discussion: Despite being medically sicker at baseline with multiple risk factors for atrial fibrillation compared to the non-statin users, the statin users displayed a consistently lower occurrence of postoperative cardiac arrhythmia in this retrospective cohort study. Statins may therefore be beneficial in the preoperative optimisation of medically complex patients undergoing THA.